Philosophy of language and poetics of Julián Ríos - Pagès, Stéphane (Tropelías: Review of Literary Theory and Comparative Literature, 2021)
On the occasion of the re-publication of Larva. Babel de una noche de San Juan (1983) by the writer Julián Ríos, an atypical and highly original early novel, which takes a number of linguistic and narratological resources to extremes, the aim is to examine and delve into the heart of this literary enterprise, which is also symptomatic of all Ríos’s work, in order to highlight the aesthetics and poetics of this writing, which corresponds to what can be called the aesthetics of simultaneity.